A research on self-efficacy beliefs, perception of success, competitive state anxieties of 9-13-year-old children playing soccer - Arıkan Ektırıcı; Ayse Feray Ozbal; Serdar Kocaeksı (Selcuk University, 2017)
The purpose of this research is to evaluation self-efficacy beliefs, perception of success and competitive state anxieties of the children that participated in youth academy selections of Anatolia University Soccer Team. In this research, totally 152 children (Age, mean: 11 ± .755) were classified in two groups as the qualified (N: 108, Age, mean: 11.02 ± .736) and the disqualified (N: 44, Age, mean: 10.95 ± .806). SES, POSQ-CH, CSAI-2C and SCAT-C were used as data collection tools in the research. The Correlations Analysis and MANOVA were employed to analyse the research data. In consequence of the conducted analysis, there is not a meaning difference (p gt;.05) among the scores of competition trait anxiety, competitive state anxiety sub-dimension and perception of success in sports sub-dimension between the qualified and the disqualified groups. There is a considerable difference between the self-efficacy scores of both groups (p lt;.05). Additionally, there is a significant negative correlation between competition trait anxiety and self-efficacy, between cognitive anxiety and self-efficacy, between cognitive anxiety and task orientation, between cognitive anxiety and task orientation and between physical anxiety and self-efficacy, physical anxiety and task orientation and between physical anxiety and ego orientation. Consequently, when selection criteria of 9-13 year-old children playing soccer are taken into consideration, only self-efficacy beliefs among the variables mentioned in this study between the qualified and the disqualified made a difference, whereas other variables did not make any differences. Once again, some relationships appear between anxiety and competence levels and perception of success.